2016
DOI: 10.1111/fwb.12700
|View full text |Cite
|
Sign up to set email alerts
|

Accounting for littoral primary production by periphyton shifts a highly humic boreal lake towards net autotrophy

Abstract: 151. The prevailing view that many humic lakes are net heterotrophic is commonly based on pelagic measurements alone. Poor light conditions in humic lakes are assumed to constrain littoral primary production (PP), such that the littoral zone has been considered an insignificant contributor to whole-lake PP. However, that assumption is based on models and inferences from pelagic processes which do not take littoral zone structure into account. 20Many lakes have an extensive ring of aquatic vegetation lying near… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
58
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 35 publications
(65 citation statements)
references
References 47 publications
7
58
0
Order By: Relevance
“…This assumption has led to the prevalent notion that littoral pri-mary producers are of minor importance in the energy budgets of humic lakes. However, we recently demonstrated that PP by littoral periphyton dominated whole-lake PP in small, highly humic Lake Mekkojärvi (Vesterinen et al 2016), contradicting predictions for the benthic fraction of whole-lake PP in such lakes according to the model presented by Vadeboncoeur et al (2008). In Mekkojärvi, the floating littoral vegetation mat fringe supports highly productive periphyton communities just under the water surface under well-illuminated conditions.…”
mentioning
confidence: 69%
See 4 more Smart Citations
“…This assumption has led to the prevalent notion that littoral pri-mary producers are of minor importance in the energy budgets of humic lakes. However, we recently demonstrated that PP by littoral periphyton dominated whole-lake PP in small, highly humic Lake Mekkojärvi (Vesterinen et al 2016), contradicting predictions for the benthic fraction of whole-lake PP in such lakes according to the model presented by Vadeboncoeur et al (2008). In Mekkojärvi, the floating littoral vegetation mat fringe supports highly productive periphyton communities just under the water surface under well-illuminated conditions.…”
mentioning
confidence: 69%
“…Mekkojärvi becomes totally anoxic during winter under ice and, therefore, cannot sustain natural fish populations. Details of the lake's physical and chemical characteristics are presented elsewhere (e.g., Devlin et al 2015, Vesterinen et al 2016. The absence of planktivorous fish normally leads to the development of dense populations of the large bodied cladoceran Daphnia longispina in summer.…”
Section: Study Lakementioning
confidence: 99%
See 3 more Smart Citations